Efektivitas Kombinasi Modalitas Elektroterapi dan Terapi Latihan pada Sprain Ankle Bilateral Grade II akibat Cedera Olahraga: Studi Kasus di Praktik Fisioterapi Mandiri Ftr. Murjito, M. Kes - Naziah Az Zahra; Putri Nur Aini; Ali Multazam; Murjito Murjito (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Ankle sprain is one of the most common musculoskeletal injuries in sports activities and often results in pain, limited range of motion, muscle weakness, and decreased functional ability. Appropriate physiotherapy management is essential to accelerate recovery and restore ankle function. This study aims to analyze the effectiveness of combining electrotherapy modalities and exercise therapy in the rehabilitation of bilateral grade II ankle sprain caused by sports injury. The research used a case study approach with physiotherapy interventions conducted through several treatment sessions. The interventions consisted of electrotherapy modalities combined with therapeutic exercises designed to reduce pain, improve joint mobility, and increase muscle strength and functional stability of the ankle. Clinical evaluation was carried out through observation of pain levels, range of motion, and functional ability during the therapy period. The findings indicated a gradual improvement in the patient’s condition, including decreased pain, increased ankle range of motion, improved muscle strength, and better functional performance during daily activities. These results suggest that the integration of electrotherapy and exercise therapy can provide a comprehensive rehabilitation approach for ankle sprain injuries. The combined intervention not only supports pain reduction but also enhances joint stability and functional recovery, enabling patients to return safely to their physical activities and reducing the risk of recurrent injury.